RELIGIJNOŚĆ W DOBIE DEGLOBALIZACJI I REWOLUCJI CYFROWEJ. SZKIC Z ZAKRESU SOCJOLOGII RELIGII I KATOLICKIEJ NAUKI SPOŁECZNEJ - Adamski, Krzysztof (Społeczeństwo, 2026)
This text seeks to map the conceptual groundwork necessary for diagnosing the religiosity of contemporary society, both in Poland and worldwide, in the era of the digital revolution. This revolution is marked by the rapid rise of social media and their owners, who possess instruments of influence over the public sphere, political power, and religious life that are at once extraordinarily precise and overwhelmingly powerful. The erosion of the classical secularization thesis has given rise to optimistic claims by leading sociologists of religion about the “return of God” to social life in modern societies. Yet the present reality appears to challenge this optimism. Rather than witnessing a revival of faith, we are confronted with frequent religious manipulations and a surge of irrationalism. In this context, what stance should the Church adopt within the framework of a proposed new social teaching? Should Christianity of the future exist as a creative minority, or should it seek to “reclaim” the lost Christianitas, amid a growing climate of apathy among the once-devout masses of Catholics and Christians of other major denominations?